2012
DOI: 10.1002/ange.201206582
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrische Katalyse mit Bis(hydroxyphenyl)diamid/Seltenerdmetall‐Komplexen

Abstract: Eine Serie von asymmetrischen Katalysatoren bestehend aus konformativ flexiblen, chiralen Amidliganden und Seltenerdmetallen wurde für die Protonentransferkatalyse entwickelt. Diese von Aminosäuren abgeleiteten Liganden bieten eine faszinierende chirale Plattform für die Bildung asymmetrischer Katalysatoren durch Komplexierung mit Seltenerdmetallen. Das Anwendungsspektrum dieser Katalysatorfamilie wurde durch die Entwicklung katalytischer Heterodimetallsysteme noch erweitert. Das Zusammenwirken von Wasserstoff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 353 publications
0
4
0
Order By: Relevance
“…Due to the differenceo fi onic radius between posttransition metals and early-transition metals( especially for rare earth metals), we envisaged that chiral ligand L2,w hich was readily obtained by ac onnection of two tridentate-Schiff-base subunits,m ay complex with early transition metals and be ap-plied in variousasymmetric reactions (Scheme 2). [6] In this communication, we found that the chiral ligand L2 indeed complexed with early transition-metal scandium(III). With this newly designed catalysts ystem, asymmetric Michael addition of nitroalkanest o2 -enoyl-pyridine N-oxides wasf irst developed with high diastereo-and enantioselectivity.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Due to the differenceo fi onic radius between posttransition metals and early-transition metals( especially for rare earth metals), we envisaged that chiral ligand L2,w hich was readily obtained by ac onnection of two tridentate-Schiff-base subunits,m ay complex with early transition metals and be ap-plied in variousasymmetric reactions (Scheme 2). [6] In this communication, we found that the chiral ligand L2 indeed complexed with early transition-metal scandium(III). With this newly designed catalysts ystem, asymmetric Michael addition of nitroalkanest o2 -enoyl-pyridine N-oxides wasf irst developed with high diastereo-and enantioselectivity.…”
mentioning
confidence: 75%
“…We found that both the newly developed ligands L2 a/L2 b and our previous ligand L3 were ablet oc atalyzet his reaction with opposite enantioselectivity,b ut when ligand L1 was employed only at race amount of product 3aa was observed. To further optimize the reactionc onditions, L2 b was chosen as an optimal ligand and the effect of solvento nt he asymmetrici nduction was also explored (entries 3,[5][6][7][8]. THF was found to be the most effective solventi nt he Michael addition in terms of the yields and levels of asymmetrici nduction.…”
mentioning
confidence: 99%
“…The winner of the 2012 prize is Masakatsu Shibasaki (Institute of Microbial Chemistry (BIKAKEN), Tokyo), who was honored for establishing the concept of cooperative asymmetric catalysis and the development of carbon–carbon bond‐forming reactions with high atom economy, as well as the catalytic asymmetric synthesis of bioactive compounds. His Review on asymmetric catalysis was featured in the Jubilee Issue of Angewandte Chemie earlier this year,1a and he has also reported in Chemistry—An Asian Journal on catalytic asymmetric addition reactions 1b. Shibasaki received his PhD in 1974 for work supervised by Shun‐ichi Yamada at the University of Tokyo.…”
Section: Featured …︁mentioning
confidence: 99%
“…[5] They are also used as ligands in stabilizing various metal centers. [6] Amide bond-forming reactions are of tremendous significance in synthetic chemistry. Therefore, amides are usually synthesized by activated carboxylic acid derivatives, [7] such as halides, [8] anhydrides, azides, or activated esters, [9] but that are mostly generated in an extra step, or using aggressive, expensive and waste-intensive reagents.…”
mentioning
confidence: 99%